PHYTOCHEMICAL TEST AND ANTIBACTERIAL ACTIVITY OF METHANOL EXTRACT OF Melicope lunu-ankenda (Gaertn.) T.G. Hartley STEM AGAINST Salmonella typhi AND Staphylococcus aureus - Hermawan, Hermawan; Wirawan, Teguh; Pratiwi, Djihan Ryn (JURNAL ATOMIK, 2021)
Phytochemical test and antibacterial activity of methanol extract of Melicope lunu-ankenda (Gaertn.) T.G. Hartley have been done. The extraction of Melicope lunu-ankenda (Gaertn.) T.G. Hartley stem sample was carried out by the maceration method using methanol as a solvent. An antibacterial activity test was carried out using the agar diffusion method. Phytochemical tests results showed that methanol extract of Melicope lunu-ankenda (Gaertn.) T.G. Hartley stem has secondary metabolites including alkaloids, steroids, triterpenoids, and quinones. The antibacterial activity test results obtained MIC values for Salmonella typhi bacteria of 1.25% and for Staphylococcus aureus bacteria of 0.625%. Methanol extract of Melicope lunu-ankenda (Gaertn.) T.G. Hartley stem has broad-spectrum antibacterial activity.